Memanfaatkan Ketokohan B. J. Habibie dalam Membangun Citra Diri Taufan Pawe sebagai Walikota Parepare - Hastira, Muh Fichriyadi; Hastira, Muhammad Fajhriyadi; Rafdi, Hashfi; Putra Pratama, M. Aviv Adhitya; Pratama, Galank; Zahir, Muh. Zuhud Al Khaer (Universitas Batanghari Jambi, 2025)
The purpose of this research is to describe how H. M Taufan Pawe uses B. J. Habibie as a symbol of his leadership and uses it to build his image. This research uses qualitative research methods with data analysis from literature related to this research. The results of this research reveal that the use of the B. J. Habibie symbol is manifested in physical development in the form of monuments and buildings that touch the community directly. The use of the name B. J. Habibie is intended to build the image of H. M. Taufan Pawe by utilizing government media and establishing relationships with external media as a means of channeling information to the public.